Rationale for the Use of Radiological Investigations; Assessment of Awareness Among Healthcare Workers of a Tertiary Care Hospital in Southern Punjab - Navera Naveed, Rameesha Musharaf, Rizwan Sadiq, Talha Sajjad, Mohammad Sufyan, Asia Rabbani, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: During recent times, radiological investigations have been playing a very beneficial role in diagnosis, confirmation and surveillance of multiple diseases in the medical science; thus increasing our diagnostic and management skills in a positive manner which was not previously possible. Now-a-days, these radiological investigations have become an integral part of our management system due to their easy availability. But this easy availability has increased the chances of misuse of these modalities as well. This cross-sectional study was aimed to assess the rationale for the use of these radiological investigations among our healthcare providers serving at Sheikh Zayed Hospital, Rahim Yar Khan. The study data was collected from study subjects via a pre-designed questionnaire from January 2022 to April 2022. Then the collected data was analyzed through SPSS software. Results of this study, including 250 study subjects (56% males and 44% females; 38.8% consultants and 61.2% PGRs/MOs), showed that the consultants primarily decide about the radiological investigations needed for the patients while the senior PGR/MO play the role in their absence. Majority of the study subjects (90%, n=225) were found well aware of the radiation hazards related to different radiological investigations. Conclusion: The healthcare providers working in different departments of SZH,RYK have enough awareness and knowledge about the rationale for the use of radiological modalities; but were not able to specify the exact limitations for the radiation doses per exposure or total dosage allowed per year to the patients associated with their harmful effects. Keywords: Knowledge; Radiological Investigations; Health Hazards; Healthcare Workers